87.1k views
5 votes
3What is the inverse of the function h(x) = - 2 + 12?h-'(x) =(2

3What is the inverse of the function h(x) = - 2 + 12?h-'(x) =(2-example-1
User Praxis
by
5.5k points

1 Answer

2 votes

We have the next function


h(x)=(3)/(4)x+12

First we need to make h(x)=y


y=(3)/(4)x+12

Then we make x=y and y=x


x=(3)/(4)y+12

Then we isolate the y


x-12=(3)/(4)y
4(x-12)=3y
y=(4(x-12))/(3)
y=(4x-48)/(3)

Therefore the inverse function is


h^(-1)(x)=(4x-48)/(3)

User Nikunj Aggarwal
by
4.6k points